Analysis of dentists' knowledge and skill levels in providing dental and oral health services to HIV/AIDS patients in Parepare City, South Sulawesi: Analisis level pengetahuan dan keterampilan dokter gigi dalam pelayanan kesehatan gigi dan mulut pasien HIV/AIDS Kota Parepare Sulawesi Selatan - Andi Anggun Mauliana Putri; Erni Marlina; Nur Asmi Usman; Harlina; Ali Yusran; Rina Masadah (Makassar Dental Journal PDGI Makassar, 2026)
HIV/AIDS remains a global health issue in Indonesia, with the city of Parepare, South Sulawesi, recording an increase in cases. The crucial role of dentists in managing HIV/AIDS patients requires optimal preparedness, which is measured by their knowledge and attitudes. This study evaluated changes in the knowledge, attitudes, and behaviour of 46 dentists in Parepare after an educational seminar and hands-on intervention. This observational study used a cross-sectional series design with questionnaires administered before and after the intervention. Data analysis used the Wilcoxon test and paired sample t-test. The intervention successfully increased the average knowledge score (p=0.162) and attitude score (p=0.876), although these increases were not statistically significant. However, the dentists' behaviour scores showed a significant increase (p=0.022), indicating the effectiveness of the intervention in triggering changes in clinical practice. It was concluded that educational seminars and hands-on training are effective in improving the behaviour of dentists in treating HIV/AIDS patients. Continuing education programmes are urgently needed to ensure improved quality of dental care for people with HIV/AIDS